Comparison between the Brix Refractometer and ELISA for Assessment of Colostrum IgG of Montbeliard x Holstein Cross Dairy Cows - N. H. Fahim; T. A. Imbabi (Faculty of Animal Science, Bogor Agricultural University, 2021)
The objectives of the present study were to examine the association between the brix refractometer% and ELISA assays in the assessment of colostrum-IgG content and in studying the factors affecting this content. Contents of IgG in colostrum samples of 132 healthy primiparous and multiparous Montbeliard x Holstein cross dairy cows kept in Egypt were evaluated using ELISA assay and brix refractometer%. The ELISA results showed that the IgG contents in the colostrum samples ranged from 5.96 to 114.84 mg/mL, with a mean of 57.07 mg/mL. Brix% results ranged from 15% to 35%, with a mean of 23.97%. The correlation and regression coefficients between ELISA(IgG) and brix% were significantly high (r=0.68 and r2 =0.59, respectively). Prediction regression equation was ELISA(IgG) = 31.81+1.12(brix refractometer%). The effects of parity and season of calving on both ELISA(IgG) and brix% were significant. ELISA(IgG) and brix% were higher in cows ≥ 3 lactations than those in the first and second lactations. Moreover, summer calving recorded higher ELISA(IgG) and brix% than autumn calving. Either ELISA(IgG) or brix% were not significantly affected by calf’s sex, single/twin births, or history of cows’ diseases. ELISA(IgG) and brix% had a significant positive correlation with calf’s birth weights and gestation lengths, while they recorded a non-significant correlation with dry-period length. It can be concluded that a refractometer is a simple on-farm tool to assess colostrum quality. Its high correlation with the lab analytical assay of ELISA confirms the validity of using refractometers by researchers in colostrum studies.